2006
DOI: 10.1021/ef0602372
|View full text |Cite
|
Sign up to set email alerts
|

Mo−Fe Catalysts Supported on Activated Carbon for Synthesis of Liquid Fuels by the Fischer−Tropsch Process:  Effect of Mo Addition on Reducibility, Activity, and Hydrocarbon Selectivity

Abstract: The effects of Mo loading (0−12 wt %) on the properties of activated-carbon- (AC-) supported Fe−Cu−K catalysts and their performance for Fischer−Tropsch synthesis are studied. Physicochemical properties studied include particle size, reducibility, and dispersion, and catalytic properties include activity, selectivity, and stability. Catalysts were characterized by N2 adsorption, energy-dispersive spectroscopy, X-ray diffraction (XRD), H2 temperature-programmed reduction (TPR), and CO chemisorption. Catalyst pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 51 publications
8
78
0
1
Order By: Relevance
“…However, Ar and H 2 decomposed Fe-Mo/MgO catalysts (SG-2 and SG-3) showed decreased pore diameter, pore volume, and surface area compared to the case of the MgO support material. This behavior can be explained as being due to pore filling and the blocking phenomenon of metal precursors [26]; this behavior supports our hypothesis that Fe-Mo systems form in a well-dispersed manner within MgO support. The product yields of carbon materials were found to be correlated with the BET surface area of the starting Fe-Mo/MgO catalysts.…”
Section: +supporting
confidence: 87%
“…However, Ar and H 2 decomposed Fe-Mo/MgO catalysts (SG-2 and SG-3) showed decreased pore diameter, pore volume, and surface area compared to the case of the MgO support material. This behavior can be explained as being due to pore filling and the blocking phenomenon of metal precursors [26]; this behavior supports our hypothesis that Fe-Mo systems form in a well-dispersed manner within MgO support. The product yields of carbon materials were found to be correlated with the BET surface area of the starting Fe-Mo/MgO catalysts.…”
Section: +supporting
confidence: 87%
“…Ma et al [16] conducted experiments at high reaction temperature (300-320°C) with activated carbon supported FeCuMoK catalysts and observed that 6% Mo (weight ratio) addition improved catalyst stability without sacrificing activity. However, in our previous work [19], it was demonstrated that 5% (weight ratio) Mo addition sharply decreased the activity of FeK/SiO 2 catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Although Mo has been excluded from ideal catalysts for FTS because it is much less active than iron and cobalt, it is still worthy to be considered as a potential promoter with additive functions. Ma et al [16] investigated the Mo loading Fe catalysts supported on activated carbon and found that Mo addition significantly improved the catalytic stability for FTS. The recent quantum chemistry calculation results [17] have proved that using Mo as promoter could increase the sulfur poisoning tolerance of Co and Fe catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) with unique structure and properties such as well-defined hollow interiors, inert surface properties, and resistance to acid and base environment have been proven to be excellent candidates as support in catalytic reactions [1][2][3][4][5][6][7] and energy storage and conversion medium [8][9][10][11]. Structural parameters of CNTs such as inner diameter, wall thickness, length, crystallinity, and electronic structure have a great influence on the performance of the supported particles or loaded matters [12][13][14][15].…”
mentioning
confidence: 99%